Tightened social distancing measures and increased violence during the COVID-19 pandemic in South Korea - Kim, Bookyoung; Son, Kyung-Bok (Frontiers in Psychology, 2023)
Introduction: In 2020, the South Korean government introduced social distancing measures, varied by region, to address the pandemic. We captured variations in social distancing measures among regions in South Korea and investigated the association between the stringency of measures and the increased incidence of violence. Methods: Incidence reports from calls to violence hotlines, including school and domestic violence and sexual harassment, from 2016–2021 were retrieved. The regional per capita incidence rates for each violence hotlines were calculated. Difference-in-difference design with fixed effects was used to elucidate different trends in the incidence rate of violence between regions with stringent social distancing measures and regions with looser measures. Results: Social distancing measures led to a decreased incidence rate of school violence and an increased incidence rate of domestic violence and sexual harassment. Different trends in the incidence of violence were noted between regions with strict social distancing measures and regions with more lenient measures. Tightened measures caused surges in domestic violence and sexual harassment. Conclusions: Social distancing measures have been an inevitable mitigation strategy against virus transmission throughout the pandemic. However, women residing in tightened social distancing measures, in particular urban areas, need more support against domestic violence.